2016
DOI: 10.1124/dmd.115.068809
|View full text |Cite
|
Sign up to set email alerts
|

Human Intestinal PEPT1 Transporter Expression and Localization in Preterm and Term Infants

Abstract: The intestinal influx oligopeptide transporter peptide transporter 1 (PEPT1) (SLC15A1) is best known for nutrient-derived di-and tripeptide transport. Its role in drug absorption is increasingly recognized. To better understand the disposition of PEPT1 substrate drugs in young infants, we studied intestinal PEPT1 mRNA expression and tissue localization across the pediatric age range. PEPT1 mRNA expression was determined using real-time reversetranscription polymerase chain reaction in small intestinal tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…In contrast to the other intestinal transporters, OATP2B1 gene expression levels were much higher in neonates than in adults . Interestingly, the localization of OATP2B1 remains questionable; 2 studies observed localization of the transporter to the apical membrane of human enterocytes, but another research group, which studied mainly pediatric intestinal tissue samples, detected OATP2B1 in the basolateral membrane . This basolateral localization was also reported by another independent group using 6 healthy human adult jejunal tissue samples .…”
Section: Ontogeny Of Membrane Transportersmentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast to the other intestinal transporters, OATP2B1 gene expression levels were much higher in neonates than in adults . Interestingly, the localization of OATP2B1 remains questionable; 2 studies observed localization of the transporter to the apical membrane of human enterocytes, but another research group, which studied mainly pediatric intestinal tissue samples, detected OATP2B1 in the basolateral membrane . This basolateral localization was also reported by another independent group using 6 healthy human adult jejunal tissue samples .…”
Section: Ontogeny Of Membrane Transportersmentioning
confidence: 67%
“…Future studies are warranted to elucidate the localization of OATP2B1 and to ascertain if it is subject to developmental changes. Using a total of 26 intestinal tissues samples, which included 19 preterm and term neonates, 1 infant 13.9 weeks old, 2 children, and 4 adolescents, Mooij and colleagues studied the developmental changes in PEPT1 mRNA expression and localization . Although PEPT1 expression appeared to be slightly lower in neonates than in their older counterparts, the tissue distribution was relatively stable among all the samples studied.…”
Section: Ontogeny Of Membrane Transportersmentioning
confidence: 99%
“…The organic anion transporting polypeptide (OATP) 2B1 uptake transporter appears to have a different ontogeny pattern compared with the transporters described earlier. OATP2B1 mRNA expression was found to be 3‐fold higher in neonates compared with adults .…”
Section: Age‐mediated Changes In Physiological Processes Determining mentioning
confidence: 95%
“…As for BCRP, data related to the multi-drug associated protein 1 (MRP1) efflux transporter are scarce and only one study reported immunodetectable protein levels comparable to adults from 7 weeks of gestation [123]. Mooij et al [125,133] reported stable mRNA expression of MRP2 from neonates to adults. The expression of influx oligopeptide transporter PEPT1 was investigated in intestinal tissue samples across the pediatric age range [133].…”
Section: Intestinal Wall Transportersmentioning
confidence: 99%
See 1 more Smart Citation